Front Cover: Optimal Pump Shaping for Entanglement Control in Any Countable Basis (Adv. Quantum Technol. 10/2021). Issue 10 (8th October 2021) - Bornman, Nicholas; Tavares Buono, Wagner; Lovemore, Michael; Forbes, Andrew
Abstract : Quantum entangled states are often produced by pumping a non‐linear crystal with a Gaussian beam and then measuring the entangled photons in some basis. In article number 2100066, Nicholas Bornman, Andrew Forbes and co‐workers show how to deterministically alter the pump light's shape for a desired output quantum state, expressed in any spatial mode basis (pattern of light). Because there are an infinite number of possible structured light patterns, their use for creation and detection of quantum states opens exciting prospects for high‐dimensional entanglement control.